Optimalisasi Kekuatan Otak Kanan untuk Belajar Berbahasa Jawa Ragam Krama di Kelas 2A SDIT AR-Raihan (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
The background that drives this research is the lack of application of manners in the language of manners that form a polite character. This is due to the use of Indonesian which is more massively used in daily communication than the use of Javanese. This research aims to be able to form a polite character in polite language by optimizing the power of the right brain. This research using a qualitative descriptive method makes the students of grade 2A SDIT Ar-Raihan as the research subjects. The research approach used is qualitative. Data collection techniques using observation, interviews, and documentation. Data analysis technique using triangulation. The results of this study indicate that optimizing the power of the right brain to learn Javanese manners can create interesting and fun learning. The process of optimizing the right brain in learning manners is through contextual learning, creating creative learning, and using electronic media. These activities are expected to help students learn Javanese manners with fun and easy to remember and can improve students' memory of the vocabulary of various manners.